2015
DOI: 10.1007/s10948-015-3145-z
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Magnetization in Mg–Zn Ferrite Nanoparticles, Prepared by Mechanochemical Processing

Abstract: One-step mechanochemical processing is one of the most useful and effective methods to produce nanoparticles. Prepared materials by this method show novel properties. In this work, Mg-substituted Zn ferrite (Mg x Zn 1−x Fe 2 O 4 ; x = 0.0, 0.2, 0.4, 0.6) nanoparticles were prepared by one-step mechanochemical processing for the first time. In addition, bulk samples with the same compositions were prepared by conventional ceramic method, which served as reference samples. The samples were characterized by the X… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Sizes of the nanoferrites were obtained in the range of 40-70 nm. Mozaffari et al [190] observed the field-emission SEM (FESEM) micrograph of Mg x Zn 1-x Fe 2 O 4 and detected particles sizes of the samples in the range of 50-100 nm and also that each particle was composed of many crystallites. Bassami's [191] TEM image of Mg 0.8 Zn 0.2-x Co x Fe 2 O 4 (0 x 0.2) revealed agglomerated round-shaped nanoparticles.…”
Section: Morphological Structurementioning
confidence: 99%
“…Sizes of the nanoferrites were obtained in the range of 40-70 nm. Mozaffari et al [190] observed the field-emission SEM (FESEM) micrograph of Mg x Zn 1-x Fe 2 O 4 and detected particles sizes of the samples in the range of 50-100 nm and also that each particle was composed of many crystallites. Bassami's [191] TEM image of Mg 0.8 Zn 0.2-x Co x Fe 2 O 4 (0 x 0.2) revealed agglomerated round-shaped nanoparticles.…”
Section: Morphological Structurementioning
confidence: 99%